Library Directors are Public Agency Administrators: Graduate Library Programs do not Prepare Librarians to become Public Administrators - Very, Diana J. (My University, 2013)
This study describes the deficiencies in American Library Association (ALA) accredited masters in library and information science (MLIS) programs in 50 institutions throughout the United States that purport to prepare librarians to become public administrators. The literature review discusses how the success of a public library is connected to the political rapport of the director with local government officials. A correlation was revealed between the budget loss due to the economic recession and the loss of professional library positions to paraprofessional positions. In researching job announcements and MLIS courses, the functions of the director positions were matched against the various courses in the MLIS programs. Some functions and skills were met by the MLIS programs in the same percentage as those needed in the job announcements, but many were not. The librarian coming from library school would not be prepared to take on management positions, although library positions without management tasks are disappearing in this economy. A recommendation from this research would be for the student to complete a dual degree for management and librarianship and work or volunteer in a public library while in school. By the completion of the program, the librarian will have several years of library experience and knowledge of both disciplines in order to start working up the career ladder in librarianship.
A Dissertation submitted to the Graduate School Valdosta State University in partial fulfillment of requirements for the degree of Doctor in Public Administration in the Department of Public Administration of the College of Political Science, May 2013
Keywords: Public Agency Administrators; Library Directors; Graduate Library Programs; Librarians; Public Administrators; American Library Association; MLIS; Certified Public Library Administrator (CPLA); Building Community; International City and County Managers Association (ICMA)